Determination of the aggregate size in detergent solution of the light-harvesting chlorophyll a/b-protein complex from chloroplast membranes - Butler, P. J. G. (1988)
The molecular mass of an oligomeric integral membrane protein, the light-harvesting chlorophyll a/b-protein complex from the photosynthetic membranes of chloroplasts, has been determined in detergent solution by analytical ultracentrifugation and measurement of the density increment at constant chemical potential of all diffusible solutes. The technique used eliminates any problems resulting from detergent binding to the protein, is independent of the particular detergent used (in this case the nonionic n-octyl β-D-glucopyranoside), and gives the apparent weight-average molecular mass at different protein concentrations, allowing extrapolation to zero concentration. It means that the solutions of the complex must be brought to dialysis equilibrium with the solvent detergent solution and also requires a reliable method for measuring the protein concentration, for which amino acid analysis was used. The detergent-solubilized complex was a trimer that dissociated into monomers and dimers at low protein concentration. The accurate concentration determinations also allowed the molar chlorophyll-to-protein ratio to be measured as 15, corresponding to 8 chlorophyll a and 7 chlorophyll b molecules.